Influence of multi-modes contest on the dynamics of a quantum dot light emitting diode - Hussein, Hawraa A.; Al Husseini, Hussein B. (Journal of optical communications, 2025)
The effects of quick mode-competition phenomena on the dynamics of semiconductor quantum dot light-emitting diode (QDLED) are the subject of theoretical investigations in this study. The analyses are based on numerical simulations of the superposed multi-mode rate equations, which take into account the inherent fluctuations related to the spontaneous emission. The modal photon number and the injected electron number are reserved correlated during the multimode sources’ numerical generating process. Based on a self-consistent model, the optical frequency effects which result in competition phenomena among lighting modes are introduced. The phenomenon of mode-competition is used to explain how noise sources affect it. Mode-competition processes cause instantaneous coupling between variations in mode intensity, which leads to instability in the dynamics of the modes and changes the state of operation. Over a broad range of carriers and photon rates (including the capture rate of the witting layer (WL) into the dot, the photon output rate in the optical mode, and the nonradiative decay rates of the number of carriers in the QD and WL), the dynamics of modes and the characteristics of the output spectrum are investigated. Three types of operation are distinguished: jittering single mode, stable single mode, and stable multimode.